Pengaruh Umur Terhadap Kadar Kholesterol, Trigliserida Dan Cooking Loss Daging Sapi Pesisir - Khasrad Khasrad (Universitas Andalas, 2006)
The research was carried out to study the effects of age to cholesterol content, trigliserida and cooking loss of meat pesisir cattle. Twelve cattle were allotted to a 4 x 3 randomized block design (RBD). The treatments are 4 levels of age, they are I1 (1.5-2.0 years), I2 (2.5-3.0 years), I3 (3.5-4.0 years) and I4 (>4.5 years). The results showed that cholesterol content of meat pesisir cattle ranged from 37.24 - 38.29 mg/100 gram, trigliserida 12.25 - 13.62 mg/100 gram of meat and cooking loss ranged from 28.10 - 32.36 %. The age of cattle didn't influence significantly (P > 0.05) to cholesterol content and trigliserida content of meat, but cooking loss persentage decreased significantly (P<0.05) by increasing the age of cattle.